2019
DOI: 10.3390/ijms21010072
|View full text |Cite|
|
Sign up to set email alerts
|

A Purified Aspartic Protease from Akkermansia Muciniphila Plays an Important Role in Degrading Muc2

Abstract: Akkermansia muciniphila can produce various mucin-degrading proteins. However, the functional characteristics of these proteins and their role in mucin degradation are unclear. Of the predicted protein-coding genes, Amuc_1434, which encodes for a hypothetical protein, is the focus in this study. A recombinant enzyme Amuc_1434 containing the 6× His-tag produced in Escherichia coli (hereinafter termed Amuc_1434*) was isolated to homogeneity and biochemically characterised. Results showed that the enzyme can hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Integrity of the mucosal barrier can be disrupted by dysbiosis of the microbiome caused by inflammation, infections, antibiotic usage, western diet, or alcohol consumption [ 41 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The mucus layer interacts with the microbiome and lower abundance of Akkermansia muciniphila was shown to decrease the mucus film [ 52 , 53 , 54 , 55 , 56 , 57 ]. An impaired gut barrier allows microbes and PAMPs to pass and reach the liver via the portal vein [ 34 ].…”
Section: Gut Permeability and Bacterial Translocationmentioning
confidence: 99%
“…Integrity of the mucosal barrier can be disrupted by dysbiosis of the microbiome caused by inflammation, infections, antibiotic usage, western diet, or alcohol consumption [ 41 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The mucus layer interacts with the microbiome and lower abundance of Akkermansia muciniphila was shown to decrease the mucus film [ 52 , 53 , 54 , 55 , 56 , 57 ]. An impaired gut barrier allows microbes and PAMPs to pass and reach the liver via the portal vein [ 34 ].…”
Section: Gut Permeability and Bacterial Translocationmentioning
confidence: 99%
“…Akkermansia muciniphila can use the sugar chain of Muc2 as a carbon source, and degrades it via the Akkermansia-muciniphila-encoded glycosidase [3]. We found that the protease encoded by Akkermansia muciniphila, Amuc_1434*, is the only currently reported protease enzyme able to degrade the Muc2 core protein [4].…”
Section: Introductionmentioning
confidence: 85%
“…Amuc_1434* protein was produced according to our previous study [4]. BCA (bicinchonininc acid) Protein Assay Kit (C503051) was purchased from Sangon Biotech Co. Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Deficiency in SBF2-AS1 expression regained the sensitivity of gemcitabine-resistant PC cells via repressing cell proliferation, migration, invasion, and EMT [ 27 ]. Both M2 macrophages and exosomes have been shown to be involved in certain phases during progression of tumors or drug resistance [ 62 64 ]. One study verified that exosomal lncRNA SBF2-AS1, which is derived from M2 macrophages of pancreatic cancer, regulates the level of X-linked inhibitor of apoptosis protein (XIAP) expression by integrating with miR-122-5p.…”
Section: Roles Of Sbf2-as1 In Diverse Cancersmentioning
confidence: 99%